PERILAKU KONSUMEN MINYAK GORENG SAWIT DI KOTA SURABAYA - Irianto, Heru (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2007)
The research aims to know (1) Consumer's need and preferences, (2) Consumer's behaviors of cooking palm oil that relation with non palm various of cooking oil in the market at Surabaya city. THis research based on descriptive method with demographic and psychographic approach to know consumer's need and preferences